2009
DOI: 10.1007/s11881-009-0023-z
|View full text |Cite
|
Sign up to set email alerts
|

Artificial grammar learning in primary school children with and without developmental dyslexia

Abstract: This paper explores implicit learning in typically developing and primary school children (9-12 years old) with developmental dyslexia using an artificial grammar learning (AGL) task. Two experiments were conducted, which differed in time of presentation and nature of the instructional set (experiment 1--implicit instructions vs experiment 2--explicit instructions). Repeated measures analysis of variance (group x grammaticality x chunk strength) showed a group effect only in experiment 1 (implicit instructions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 59 publications
2
26
2
Order By: Relevance
“…Recently, Arciuli and Simpson [27] found age effects in a visual statistical learning task carried out in children between 5 and 12 years of age and showed that they occurred regardless of the durations of presentation of the stimuli. Developmental influences were also reported in a study comparing artificial grammar learning in typically developing children and children with developmental dyslexia [28].…”
Section: Introductionmentioning
confidence: 83%
“…Recently, Arciuli and Simpson [27] found age effects in a visual statistical learning task carried out in children between 5 and 12 years of age and showed that they occurred regardless of the durations of presentation of the stimuli. Developmental influences were also reported in a study comparing artificial grammar learning in typically developing children and children with developmental dyslexia [28].…”
Section: Introductionmentioning
confidence: 83%
“…Such a relationship is expected according to the theory that there exists a general statistical learning ability that is linked to reading ability (Arciuli & Simpson, 2012; Jiménez-Fernández et al, 2011; Pavlidou & Williams, 2010; Pavlidou et al, 2009; Vicari et al, 2005; Vicari et al, 2003). We did not find a relationship of this sort.…”
Section: Discussionmentioning
confidence: 99%
“…A large degree of asymmetry may be a sign of good statistical learning ability, which according to some investigators is a domain-general ability that is linked to literacy skill (Jiménez-Fernández, Vaquero, Jiménez, & Defior, 2011; Pavlidou, Williams, & Kelly, 2009; Pavlidou & Williams, 2010; Vicari et al, 2005; Vicari, Marotta, Menghini, Molinari, & Petrosini, 2003). For example, Vicari et al (2003) had participants press a key whenever a green circle appeared on a screen.…”
mentioning
confidence: 99%
“…Individuals with dyslexia are impaired at a variety of tasks believed to be sub-served by procedural learning including motor adaptation (Brookes, Nicolson, & Fawcett, 2007), implicit sequence learning (Howard et al, 2006; Vicari, Marotta, Menghini, Molinari, & Petrosini, 2003), probabilistic category learning (Gabay, Vakil, Schiff, & Holt, in press), and artificial grammar learning (Pavlidou, Williams, & Kelly, 2009). Procedural learning among individuals with dyslexia is less stable, more prone to interference (Gabay, Schiff, & Vakil, 2012b), and less effectively consolidated (Gabay, Schiff, & Vakil, 2012a).…”
Section: Introductionmentioning
confidence: 99%